1982
DOI: 10.1002/ajim.4700030203
|View full text |Cite
|
Sign up to set email alerts
|

The role of macrophages and immunocytes in the pathogenesis of pulmonary diseases due to mineral dusts

Abstract: There is considerable evidence of generalized stimulation of the immune system in pulmonary dust diseases. This stimulation involves both the T- and the B-arms of the immune system. A reasonable explanation of this immune stimulation resides in an effect of the mineral dusts on the macrophages. This effect is likely to be mediated by the production of interleukin-1. Since the same substance also stimulates fibroblasts, a unified view of the pathogenesis of pulmonary dust diseases is now possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…It has been suggested that mineral dusts and silica can stimulate the production of IL-1 (11,12) which might explain the immunomodulatory properties recorded here for the respirable fraction of the Marra Mamba iron ore dust. However our preliminary studies to detect an endogenous increase in IL-1 production following iron ore injection have proved to be largely negative (Table 1).…”
Section: -7+110mentioning
confidence: 63%
See 1 more Smart Citation
“…It has been suggested that mineral dusts and silica can stimulate the production of IL-1 (11,12) which might explain the immunomodulatory properties recorded here for the respirable fraction of the Marra Mamba iron ore dust. However our preliminary studies to detect an endogenous increase in IL-1 production following iron ore injection have proved to be largely negative (Table 1).…”
Section: -7+110mentioning
confidence: 63%
“…While the silica content of dusts determines to a large degree their direct cytotoxic activity for both macrophages and to a lesser degree neutrophils (10), there have been reports of adjuvantlike properties for iron ore dusts and silica (5,11,12) which may result from the induction of interleukin-l (IL-1) from dust loaded macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it is the same damage to macrophages, due to properties of silica particles not yet fully understood, that serves as a trigger mechanism for enhanced fibrogenesis (11,12) and possibly the immunopathologic components of silicosis. However, there is also a hypothesis stating that the immunopathology of silicosis is due to stimulation of the macrophage (13,14). Thus, the quartz-macrophage interaction serves not only as a connecting link between the provisionally outlined first stage of the silicosis pathogenesis and its consequent steps, but plays a key role in this process as a whole.…”
Section: Some Theoretical Premises Of Pathogenesismentioning
confidence: 99%
“…Nearly all authors who conducted investigations comparing the incidence and the time of development of silicosis in men and women who had been working in presumably equal conditions concluded that women are more predisposed to this disease (13,(44)(45)(46). The fact that some characteristics of the male working populations (e.g., smoking, overindulging in alcohol, chronic bronchitis, etc.)…”
Section: Sex-dependent Predispositionmentioning
confidence: 99%
“…This was confirmed when Collis observed that workers exposed to quartz died much more frequently of tuberculosis than those with other kinds of dust exposure. Even against this background, elucidation of the mechanisms of silica's biological properties is still incomplete; while we have advanced our knowledge of these particles' intracellular activity (3), much study is now directed to membrane effects (4) and the question of immunological mechanisms (5).…”
mentioning
confidence: 99%